Dose-Dependent Effects of Remimazolam on Early Perioperative Neurocognitive Disorders in Elderly Colorectal Cancer Patients Undergoing Laparoscopic Surgery - Liu Z; Zhang X; Wang X; Liu Z; Pang Y (Drug Design, Development and Therapy)
Zhenqi Liu, Xinyu Zhang, Xuebing Wang, Ziyang Liu, Yong Pang Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong City, Sichuan Province, People’s Republic of ChinaCorrespondence: Yong Pang, Department of Anesthesiology, Affiliated Hospital of North Sichuan Medical College, Nanchong City, Sichuan Province, People’s Republic of China, Tel +86 18784295942, Email ppangpang111@163.comObjective: To study the effect of different doses of remimazolam on the maintenance of anesthesia and its impact on postoperative cognitive function in elderly patients undergoing laparoscopic colorectal surgery.Methods: A total of 120 elderly patients scheduled for laparoscopic colorectal surgery under general anesthesia (both sexes included, ASA grade (II–III) were randomly assigned to experimental groups (R1-R3) and control group (P), with 30 cases per group. The experimental groups received different remimazolam maintenance doses: R1 (0.5 mg/kg/h), R2 (1.0 mg/kg/h), and R3 (1.5 mg/kg/h), while the control group received propofol for sedation. Perioperative cognitive function was evaluated using MMSE (Mini-Mental State Examination) and MoCA (Montreal Cognitive Assessment) preoperatively, and on postoperative days 3 and 7, to analyze differences in cognitive effects and safety profiles of remimazolam across the four groups.Results: A total of 117 patients were ultimately included, with 3 excluded due to intraoperative conversion to open surgery. Participants were randomly allocated into four groups according to remimazolam maintenance dosing regimens: 30 in the R1 group, 28 in the R2 group, 30 in the R3 group, and 29 in the P group.There was no statistically significant difference in postoperative cognitive function scores between the R2 and R3 groups, and both groups had scores that were significantly higher than those of the R1 and P groups, with statistically significant differences.Conclusion: Compared to propofol, remimazolam at medium and high doses can reduce the incidence of perioperative neurocognitive dysfunction in elderly patients. High-dose remimazolam anesthesia maintenance may prolong extubation time, increase the incidence of postoperative shivering, and potentially lead to re-sedation after awakening, so medium-dose remimazolam is more suitable for intraoperative anesthesia maintenance in elderly patients without increasing the incidence of adverse events.Keywords: remimazolam, general anesthesia, elderly, cognitive function